Pharmaceutical Advertising in Libya: Legal Foundations and the Urgent Need for Drug Scheduling Reform - Ramadan Elkalmi (AlQalam Journal of Medical and Applied Sciences, 2025)
Libya’s pharmaceutical sector faces a critical regulatory imbalance. While advertising is governed by a patchwork of laws and ministerial decisions, the country lacks a formal drug scheduling system to guide prescribing and dispensing practices. This commentary reviews the legal foundations of pharmaceutical promotion, identifies the consequences of unregulated prescribing, and advocates for the urgent establishment of a national drug scheduling framework. Drawing on international models and ethical imperatives, the article calls for integrated reform to protect public health, ensure responsible marketing, and promote rational pharmacotherapy in Libya’s evolving healthcare landscape.